The Impact of Virtual Reality Games on Reducing Motor and Cognitive Disorders in Children with Autism Spectrum: A Meta-Analytical Review - Mazaheri, AmirHossein; Tarkhan, Alireza; Mirakhori, Fateme (AI and Tech in Behavioral and Social Sciences, 2024)
Autism spectrum disorder (ASD) is one of the neurodevelopmental disorders (NDs) characterized by poor social skills, delayed speech development, and a tendency towards engaging in repetitive and stereotypical behaviors which make the participation of affected individuals difficult in educational settings. This disorder includes a wide range of neurodevelopmental issues such as Asperger’s syndrome and autism. The present research is a meta-analysis review that involved collecting, categorizing, and summarizing scientific works related to the effects of virtual reality (VR) games and exergames on the motor skills of children with ASD and NDs, spanning from 2011 to 2022, derived from scientific databases including Google Scholar, Scopus, and PubMed using keywords such as NDs, ASD, VR games and exergames. The search method involved entering the mentioned keywords for papers published between 2011 and 2022 and those without full-text accessibility were excluded from the study. Consequently, ten highly cited papers were selected for review and analysis. According to the conducted studies, the results indicate a positive impact of VR games on the symptoms of participants with ASD. Exergames and VR can be utilized as therapeutic interventions to reduce symptoms in individuals with ASD.